Answer:
The coefficient of a²b³c is -720
Explanation:
Given:
![(2a-b+3c)^6](https://img.qammunity.org/2020/formulas/mathematics/college/l6b3l0i3jveaxtg8t8etmmdm2htri15192.png)
Let 2a-b = x and 3c = y
![(x+y)^6](https://img.qammunity.org/2020/formulas/mathematics/college/quhm4z3bjup8ewtmb5eq4kae87o0567xme.png)
General term of binomial expansion.
where, n=6 , r=1 ( because exponent of c is 1)
![\Rightarrow ^6C_1x^(6-1)y^1](https://img.qammunity.org/2020/formulas/mathematics/college/p8c6kt1xu5b7gl9u49wurhpsdlv7qls1re.png)
![\because y=3c, x=2a-b](https://img.qammunity.org/2020/formulas/mathematics/college/2qsqoonspoq0f1967bs6lnlauctd20tsxw.png)
----------(1)
Now, we simplify (2a-b)⁵
![T_(r+1)=^5C_r(2a)^(5-r)(-b)^r](https://img.qammunity.org/2020/formulas/mathematics/college/pbmlp0em8q07w46b06izblujxowcjeozrc.png)
The exponent of b is 3 and a is 2 .
If we take r=3 will get exponent of b is 3 and a is 2
So, put r=3
![T_(4)=^5C_3(2a)^(2)(-b)^3=-40a^2b^3](https://img.qammunity.org/2020/formulas/mathematics/college/5hwwwekrtfmndbbthqnqp2l59ge6gdw3by.png)
Substitute into equation (1)
![\Rightarrow 18\cdot -40a^2b^3c](https://img.qammunity.org/2020/formulas/mathematics/college/8izuve74pi7f07y7tlx1pq37wqjaal5te5.png)
![\Rightarrow -720a^2b^3c](https://img.qammunity.org/2020/formulas/mathematics/college/r73nf3d4yw78e5w1inw5m6d5vni82hdtjz.png)
Hence, The coefficient of a²b³c is -720